Diagnosis of infant synostotic and nonsynostotic cranial deformities: a review for pediatricians - Enrico Ghizoni; Rafael Denadai; Cesar Augusto Raposo-Amaral; Andrei Fernandes Joaquim; Helder Tedeschi; Cassio Eduardo Raposo-Amaral
Abstract Objective: To review the current comprehensive care for nonsyndromic craniosynostosis and nonsynostotic cranial deformity and to offer an overall view of these craniofacial conditions. Data source: The review was conducted in the PubMed, SciELO, and LILACS databases without time or language restrictions. Relevant articles were selected for the review. Data synthesis: We included the anatomy and physiology of normal skull development of children, discussing nuances related to nomenclature, epidemiology, etiology, and treatment of the most common forms of nonsyndromic craniosynostosis. The clinical criteria for the differential diagnosis between positional deformities and nonsyndromic craniosynostosis were also discussed, giving to the pediatrician subsidies for a quick and safe clinical diagnosis. If positional deformity is accurately diagnosed, it can be treated successfully with behavior modification. Diagnostic doubts and craniosynostosis patients should be referred straightaway to a multidisciplinary craniofacial center. Conclusions: Pediatricians are in the forefront of the diagnosis of patients with cranial deformities. Thus, it is of paramount importance that they recognize subtle cranial deformities as it may be related to premature fusion of cranial sutures.